2020
DOI: 10.15252/embr.202051252
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 evades immune detection in alveolar macrophages

Abstract: Respiratory infections, like the current COVID-19 pandemic, target epithelial cells in the respiratory tract. Alveolar macrophages (AMs) are tissue-resident macrophages located within the lung. They play a key role in the early phases of an immune response to respiratory viruses. AMs are likely the first immune cells to encounter SARS-CoV-2 during an infection, and their reaction to the virus will have a profound impact on the outcome of the infection. Interferons (IFNs) are antiviral cytokines and among the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 37 publications
19
71
0
2
Order By: Relevance
“…Using immunolabeling, we detected CD169 1 alveolar macrophages (AMs) and Ly6G 1 neutrophils in the lungs of infected mice. AMs have been shown to play a critical role in the initiation of a cytokine storm in severe COVID-19, and reports have shown that they are susceptible to infection with SARS-CoV-2 (19)(20)(21). Neutrophils, which have also been shown to play a role in lung inflammation during SARS-CoV-2 infection through the release of neutrophil extracellular traps (NETs) were detected in the parenchyma, although in lower numbers, and were more sparsely distributed than AMs (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Using immunolabeling, we detected CD169 1 alveolar macrophages (AMs) and Ly6G 1 neutrophils in the lungs of infected mice. AMs have been shown to play a critical role in the initiation of a cytokine storm in severe COVID-19, and reports have shown that they are susceptible to infection with SARS-CoV-2 (19)(20)(21). Neutrophils, which have also been shown to play a role in lung inflammation during SARS-CoV-2 infection through the release of neutrophil extracellular traps (NETs) were detected in the parenchyma, although in lower numbers, and were more sparsely distributed than AMs (22,23).…”
Section: Resultsmentioning
confidence: 99%
“…Several immune cell populations in the lungs have been found to play vital roles in the response to respiratory virus infection (Channappanavar et al, 2016;Dalskov et al, 2020;LeMessurier et al, 2020). We therefore sought to determine if any of the genetic loci identified in our study showed an association with influenza A virus (IAV)-induced disease phenotypes.…”
Section: Relationships Between Baseline Immune Lung Qtl and Respiratomentioning
confidence: 94%
“…Assessment of Avo1 expression was performed by re-searching LC-MS/MS data from two previously published SARS-CoV-2 studies looking at the infection of human alveolar macrophages [26] and green monkey Vero E6 cells [27]. Data were either search against the human or green monkey SWISS-PROT [28] reference proteomes (Human db: 09-2020, 20609 sequences; Green monkey: 08-2020, 19229 sequences) and the UNIPROT [29] SARS-CoV-2 database (12-2020, 16 sequences) to which the putative Avo1 protein sequence had been included.…”
Section: Methodsmentioning
confidence: 99%